The EMU and the anchoring of inflation expectations? - Mayes David; Paloviita Maritta; Viren Matti (Aboa Centre for Economics (ACE), 2015)
It has been argued that one advantage of EMU in the EU has been an improvement in the credibility of monetary policy. This paper provides a new way of assessing the credibility of monetary policy by analyzing the dispersion of inflation-unemployment observations over time. In this way, we may reveal whether the short run Phillips curves have shifted due to changes in inflation expectations. This way of analyzing the anchoring of inflation expectations is both simple and free from ambiguities that are related to the choice of the Phillips curve specification and modelling of inflation expectations. The analysis uses data from eleven EMU countries and nine non-EMU countries that are used as points of comparison. The sample periods are 1984-1998 and 1999-2013. The analysis is based on dispersion measures where we use alternative weights for inflation and unemployment and also on a simple Misery index which is just a sum of inflation and unemployment values. The general outcome of the paper is that dispersion (and the Misery index) has decreased during the EMU period. The decrease has, however, been smaller than in control group countries. This implies that while the credibility of monetary policy may have increased under EMU, this just mirrors the general experience in the OECD over the same period.
Keywords: E31; E61; 330; Misery-index; inflation; unemployment; Phillips curve